Reading Political Intrigue In A Book “Pesan Dari 8 Negeri” - Moch. Imron Rosyidi; Imam Sofyan (ARISTO, 2023)
Pesan Dari 8 Negeri is a fairly comprehensive book on political reflection. It starts with a story from the west with the story of Brutus as a symbol of political stupidity which becomes a common thread that political events are indeed very dynamic. Interestingly, the term Brutus syndrome appears to distinguish this book from several other references that discuss politics. In addition, the phrase judl explicitly shows that politics is the culture of society by choosing the phrase "country" rather than "state". In addition, politics in the historical aspect can be displayed in a flowing language style that is effectively attached to the reader's mind.